The Implementation of Simultaneous Village Head Implementation Policy in Realizing Participatory, Transparent and Accountable Election Process in Indonesia - Wawan Munawar Kholid (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
The purpose of this research is to Analyze the implementation of the simultaneousVillage Head election policy in realizing a participatory, transparent and accountableelection process in Bogor Regency and Arrange a new model of implementing theVillage Head Election policy simultaneously in realizing a participatory, transparentand accountable election process in Bogor Regency. This study uses a qualitativeresearch approach with 21 (twenty-one) informants as a snowball technique.Secondary data collection using literature study techniques, and primary data usinginterview and observation techniques. Implementation of Pilkades policysimultaneously in realizing the process of participatory selection, transparency, andaccountability. The implementation of the village head election policy simultaneouslyin realizing the participatory, transparent and accountable election process in BogorRegency is not optimal because there are still many problems found. The new modelarranged is called the Sultaa Model, this model consists of elements of participation,transparency, and accountability. The model can be applicable if it meets severalrequirements, namely qualified human resources, adequate facilitation, adequatefunding, and effective supervision.